Elites and society - Bottomore, T. B., 1920-1992 (Routledge, 1993)
In this substantially revised second edition of a classic text, Tom Bottomore reconsiders élite theory in the light of recent studies. He examines its role in relation to class structures, and considers the prospects for a more equal society.